Formulation And Development Of Colon Specific Drug Delivery Using Dextrin - PRIYANKA S. CHAUDHARI,; K.S. SLUNKHE,; P. P. AMRUTKAR,; DR. S. V.CHAUDHARI,; DR.R.J.OSWAL, (International Journal of Pharma and Bio Sciences, 2012)
The objective of the present study is to develop colon targeted drug delivery system by using polysaccharide as a carrier. Matrix tablets containing various excipients and polysaccharide were prepared by wet granulation technique using different binder systems. The matrix tablets were evaluated by different IPQC tests, content uniformity, matrix index and in vitro drug release study as per IP 1996 method. Drug index profile in simulated gastric and intestinal fluid was evaluation parameter for selecting the best formulation. Drug release profile in simulated gastric, intestinal fluid from the dissolution studies was taken for selecting the best formulation. The matrix tablet containing dextrin as a carrier and ethyl cellulose as a binder found to be suitable for targeting paracetamol for local action in the colon. Same matrix tablets released fewer amounts (8-11%) of drug in simulated gastric fluid. Matrix tablets containing dextrin released 95-98 % of paracetamol in simulated colonic fluid with 4 % human fecal matter solution.